SNP G-1082A IL-10 GENE: ALLELE AND GENOTYPE DISTRIBUTION OF PERIODONTITIS PATIENT IN YOGYAKARTA: SNP G-1082A GEN IL-10: DISTRIBUSI ALEL DAN GENOTIP PADA PASIEN PERIODONTITIS DI YOGYAKARTA - Sari, Rezmelia; Prayitno, Prayitno; Fadhilah, Alya Nur (TALENTA, 2016)
Periodontitis is multifactorial inflamation process and related to disproportion of cytokine. IL-10 is a dominant noninflammatory cytokines that related to gene polymorphism. Polymorphism G-1082A IL-10 genes has been reported to increase the risk of periodontitis occurs in Italian populations, apart from different result found in Brazilian. The purpose of this research was to determine the polymorphism G-1082A IL-10 in periodontitis patients in Indonesia, especially among Yogyakarta’s Javanese. This is a case-control research with subjects according to the inclusion criteria. DNA was taken by cotton swab from the epithelial cells of buccal mucosa, and was isolated using a PrestoTM (GeneAid) kit. Genotyping analysis by using the PCR RFLP technique and descriptive results were presented. The result showed that A allele frequency is 100% and no G allele was found. AA genotype in case group has lower frequency than in control group and vice versa. From this research, it was concluded that A allele was dominant in Yogyakarta’s Javanese, and AA genotype frequency is lower in individual with periodontitis.